The relationship between parental abuse with parental and marital roles attitude in girls - Nafisehsadat Nekuei; Akram Zirakidana; Ashraf Kazemi; Nastaran Mohhamad Ali Beigi; Masoomeh Alijanpoor (Wolters Kluwer Medknow Publications, 2017)
Background: Gender role attitude pertains to individuals' attitude toward proper role activities for men and women. Most of the factors relevant to family and society may affect individuals' attitudes toward their role. Meanwhile, parents' behaviors can act as an important factor in formation of different dimensions of children's personality. Accordingly, the present study was aimed to investigate the relationship between maltreatment and girls' attitudes toward parental and marital roles. Materials and Methods: This cross-sectional correlational study was conducted in Isfahan University of Medical Sciences in 2013 with 190 female students as the sample. Participants were selected using the random-proportional sampling method. A demographic questionnaire, researcher-made maltreatment questionnaire, and Homami's gender role attitudes questionnaire were used as the data collection instruments. Data were analyzed using Chi-square, Kruskal-Wallis, and Mann-Whitney tests. Results: Results indicated that the feminine attitude was the dominant attitude in gender roles. Findings also revealed no significant correlation between the type of gender role attitude in parental role and maltreatment. However, the correlation was meaningful in marital role of sexual and fertility affairs (P = 0.02). Conclusions: Results revealed that participants had traditional female attitudes toward their gender roles in two aspects. First, taking the cultural domination on attitudes into account, that type of attitude is appreciated in which the individual feels relaxed and has an acceptable performance in the society. Furthermore, to promote certain types of attitudes, the entire socio-cultural and economic dimensions of the society must be taken into account. Family and social policy makings are regarded as starting points for different attitudes toward maltreatment.